Determining performance characteristics of an NGS‐based HLA typing method for clinical applications. (16th February 2016) - Duke, J. L.; Lind, C.; Mackiewicz, K.; Ferriola, D.; Papazoglou, A.; Gasiewski, A.; Heron, S.; Huynh, A.; McLaughlin, L.; Rogers, M.; Slavich, L.; Walker, R.; et al.
Abstract: This study presents performance specifications of an in‐house developed human leukocyte antigen (HLA) typing assay using next‐generation sequencing (NGS) on the Illumina MiSeq platform. A total of 253 samples, previously characterized for HLA‐A, ‐B, ‐C, ‐DRB1 and ‐DQB1 were included in this study, which were typed at high‐resolution using a combination of Sanger sequencing, sequence‐specific primer (SSP) and sequence‐specific oligonucleotide probe (SSOP) technologies and recorded at the two‐field level. Samples were selected with alleles that cover a high percentage of HLA specificities in each of five different race/ethnic groups: European, African‐American, Asian Pacific Islander, Hispanic and Native American. Sequencing data were analyzed by two software programs, Omixon'starget and GenDx'sNGSengine . A number of metrics including allele balance, sensitivity, specificity, precision, accuracy and remaining ambiguity were assessed. Data analyzed by the two software systems are shown independently. The majority of alleles were identical in the exonic sequences (third field) with both programs for HLA‐A, ‐B, ‐C and ‐DQB1 in 97.7% of allele determinations. Among the remaining discrepant genotype calls at least one of the analysis programs agreed with the reference typing. Upon additional manual analysis 100% of the 2530 alleles were concordant with the reference HLA genotypes; the remaining ambiguities did not exceed 0.8%. The results demonstrate the feasibility and significant benefit of HLA typing by NGS as this technology is highly accurate, eliminates virtually all ambiguities, provides complete sequencing information for the length of the HLA gene and forms the basis for utilizing a single methodology for HLA typing in the immunogenetics labs.